Bacopa monnieri, a wonder plant in the backyard: Emphasizing the role of the microbiome in increasing its potential - Himani Barthwal; Charu Sharma; Vijay Kumar; Vishal Rajput; Bindu Naik; Shivesh Sharma; Sushila Devi; Vivek Kumar (Phytomedicine Plus)
Recently, the utilization of natural or herbal products has increased worldwide. Various naturally isolated plant products have been assessed as therapeutics for the treatment of a variety of diseases. Microbes are related to medicinal plants and have enormous potential in the context of promoting plant growth traits and producing active ingredients of therapeutic importance. Bacopa monnieri, also called ‘Brahmi’ and water hyssop, has been utilized extensively in the ayurvedic system of medicine for a long time. Phytochemical investigations of B. monnieri extracts have revealed the occurrence of several active compounds, such as bacosides, alkaloids and triterpenoids. All these active chemical ingredients act as the best memory enhancer and are also used for various illnesses. The microbially mediated production of novel secondary metabolites with key biological activities could be an alternative method to obtain bioactive ingredients. This review highlights the interactions between microbes and the medicinal plant B. monnieri, illuminating the creation of biologically active compounds with medicinal importance within the plant.